2011
DOI: 10.1088/0004-637x/740/2/78
|View full text |Cite
|
Sign up to set email alerts
|

CANGAROO-III OBSERVATION OF TeV GAMMA RAYS FROM THE UNIDENTIFIED GAMMA-RAY SOURCE HESS J1614–518

Abstract: We report the detection, with the CANGAROO-III imaging atmospheric Cherenkov telescope array, of a very high energy gamma-ray signal from the unidentified gamma-ray source HESS J1614−518, which was discovered in the H.E.S.S. Galactic plane survey. Diffuse gamma-ray emission was detected above 760 GeV at the 8.9σ level during an effective exposure of 54 hr from 2008 May to August. The spectrum can be represented by a power law: (8.2 ± 2.2 stat ± 2.5 sys ) × 10 −12 × (E/1 TeV) −γ cm −2 s −1 TeV −1 with a photon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…and CANGAROO-III [38] telescopes have found several high energy gamma-ray sources in IceCube's FOV. Most of these sources are identified as or correlated with PWNe.…”
Section: Discussionmentioning
confidence: 99%
“…and CANGAROO-III [38] telescopes have found several high energy gamma-ray sources in IceCube's FOV. Most of these sources are identified as or correlated with PWNe.…”
Section: Discussionmentioning
confidence: 99%
“…This SNR scenario was further investigated by Mizukami et al (2011). By assuming a power-law distribution of a population of accelerated protons and a source distance of 10 kpc, an ambient matter density of 100 cm −3 was required to reproduce the γ-ray spectrum of HESS J1614−518 via a hadronic interaction model.…”
Section: Hess J1614−518mentioning
confidence: 99%
“…A possible association between HESS J1614−518 and the young open stellar cluster Pismis 22 (Piatti et al 2000) was suggested in scenarios where stellar winds from several B-type stars or undetected SNRs from deceased members of the cluster would accelerate cosmic-rays that would interact with ambient gas to produce γ-rays hadronically. Mizukami et al (2011) used the CANGAROO-III telescopes to study the TeV γ-ray emission towards HESS J1614−518, and also investigated the plausibility of several radiation mechanisms. A leptonic scenario based on an undetected SNR was rejected as it was not able to reproduce the observed spectral energy distribution (SED) in γ-rays.…”
Section: Introductionmentioning
confidence: 99%
“…This double-peaked structure is also hinted at in the LAT counts map in Figure 19 but is not very significant. The TeV source was also detected by CANGAROO-III (Mizukami et al 2011).…”
Section: Fgl J16152−5138mentioning
confidence: 99%
“…Source A is an extended source consistent with the peak of HESS J1614−518 and source B coincident with Pismis 22 and toward the center but in a relatively dim region of HESS J1614−518 (Matsumoto et al 2008). Three hypotheses have been presented to explain this emission: either source A is an SNR powering the γ -ray emission; source A is a PWN powered by an undiscovered pulsar in either source A or B; and finally that the emission may arise from hadronic acceleration in the stellar winds of Pismis 22 (Mizukami et al 2011).…”
Section: Fgl J16152−5138mentioning
confidence: 99%